2004
DOI: 10.1023/b:biop.0000047164.06779.27
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Growth and Shoot Multiplication of Achras zapota in a Controlled Carbon Dioxide Environment

Abstract: The culture vessels with multiplying shoots of Achras zapota L. on Schenk and Hildebrandt (SH) medium containing 8.88 µM 6-benzylaminopurine (BAP) with or without sucrose were kept under varied CO 2 concentrations ranging from 0.6 to 40.0 g m -3 using different concentrations of sodium bicarbonate (NaHCO 3 ), sodium carbonate (Na 2 CO 3 ), potassium bicarbonate (KHCO 3 ), and potassium carbonate (K 2 CO 3 ) in small acrylic chambers. Complete absence of carbon source caused death of shoots within 20 d. Under e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…[50][51][52] In the present investigation, the combination of 3.0% sucrose and controlled and enriched CO 2 environment proved to be a better option for in vitro shoot growth and multiplication in C. paniculatus. Similar synergistic effects of combinations of sucrose and CO 2 on in vitro shoot growth were observed in tobacco, 53 Wrightia tomentosa, 31 apple, 54 C. papaya 46 and Actinidia deliciosa. 55 Besides this, it was also observed that liquid medium was superior in overall growth over semi-solid medium in CO 2 -enriched conditions.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…[50][51][52] In the present investigation, the combination of 3.0% sucrose and controlled and enriched CO 2 environment proved to be a better option for in vitro shoot growth and multiplication in C. paniculatus. Similar synergistic effects of combinations of sucrose and CO 2 on in vitro shoot growth were observed in tobacco, 53 Wrightia tomentosa, 31 apple, 54 C. papaya 46 and Actinidia deliciosa. 55 Besides this, it was also observed that liquid medium was superior in overall growth over semi-solid medium in CO 2 -enriched conditions.…”
Section: Discussionsupporting
confidence: 66%
“…24,27 Enhanced plantlet growth and multiplication under controlled carbon dioxide enriched environment have been achieved in a number of herbaceous, 28,29 and woody plants. [30][31][32][33][34][35][36] The present study was undertaken hypothesizing that the liquid medium and CO 2 enrichment could synergistically affect the in vitro growth of C. paniculatus, both in terms of rate of multiplication as well as their photosynthetic efficiency. It was also assumed that the plantlets obtained would be of better quality having strong potential of their survival during ex vitro transplantation.…”
Section: Introductionmentioning
confidence: 99%